Persepasi pelanggan terhadap aplikasi tahap perkhidmatan dalam pengurusan penyelenggaran fasiliti di institusi pengajian tinggi - Kadir, Zanariah (2007)
A quality and systematic maintenance management will definitely give good impact and help to establish a good name for service provider and the stakeholder. To ensure the quality of services are sustained and appreciated by the customers, a mechanism has been introduced which known as Service Level Agreement (SLA) where commonly known as Perjanjian Tahap Perkhidmatan (PTP). SLA is an agreement that involves customers and service provider for the purpose of helping both parties to understand the mechanism of services that being provided. So, a study is held in collaboration with UTM Skudai, Johor, where PTP is being introduced to Unit Penyelenggaraan, Bahagian Harta, Pejabat Harta Bina (UPBH-PHB), a department that is authorized to manage the facilities maintenance for the UTM campus. Two main objectives are set for the study and they are; To identify opinions and perceptions of customers towards PTP and To set up SLA as one of a system for maintenance management of landscaping and cleanliness of the campus. All data are collected through literature study, interview and survey methods between Bahagian Harta staffs, people who involve in managing student hostels and contractors. Literature study is being organized to get primary data through journals and other references about SLA proposals for maintenance management. The results from the study are some findings to achieve the objectives and form the SLA structure. Thus a number of proposals have been made suggested in order to help UPBH-PHB in achieving its goals that is to adopt PTP as a mechanism in developing a world class and competitive management system.